Etika Guru dalam Perspektif Sayyid Usman: (1238-1332 H/1822-1914 M) - Harahap, Radinal Mukhtar (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2019)
The discussion on teacher ethics has been the subject of discussion among Muslim scholars and scholars and has generated many insights including the views of the great scholars Sayyid Usman. He is a Muslim scholar who has done extensive research in Islamic Education. This paper attempts to address Sayyid Usman's perspective on teacher ethics. It is in his view that, personally, the teacher should be sincere, wara', zuhud, tawadhu', not 'say, no takabur, not riyâ', and not malicious. A teacher must master the material he teaches, know the requirements of knowledge, and even know where to find the knowledge he has, and practice it. So that a teacher can teach the knowledge he has to the learners with the aim of not only being good in the eyes of the religion but also good in the customs of his country. As a result, efforts to improve the quality of a teacher need to be constantly developed. Therefore, the rules of the Indonesian Teacher Ethics Code should be of concern for the creation of the best generation of the nation's successor.